Proterozoic orogens of the northeastern Canadian Shield: new information from the Lithoprobe ECSOOT crustal reflection seismic survey - Hall, Jeremy; Wardle, Richard J.; Gower, Charles F.; Kerr, Andrew; Coflin, Kevin; Keen, Charlotte E.; Carroll, Peter (Canadian Journal of Earth Sciences, 1995)
As part of the Eastern Canadian Shield Onshore–Offshore Transect (ECSOOT), Lithoprobe acquired 1250 km of deep seismic reflection data along the coast of Labrador and across Ungava Bay, to image evidence of Proterozoic crustal accretion to the Archean nuclei of the Nain and Superior provinces of the Canadian Shield. The relatively pristine Archean crust of the Nain Province has low reflectivity and generally lacks systematic reflector orientations. Reworking of Archean crust on the margins of the Makkovik Province has little effect on this weak signature. In contrast, the Archean crust in the Eastern Churchill (Rae) Province appears to have been overprinted by a strongly developed, whole-crustal, easterly dipping reflection fabric, interpreted to result from Proterozoic collision of the Nain and Superior provinces in the paired New Quebec and Torngat orogens. Juvenile Proterozoic crust in the Makkovik and Grenville provinces also shows strong whole-crustal dipping reflection fabrics, interpretable as outwardly verging structures associated with collisional mobile belts. Crustal thickness varies from 35 to 45 km in Proterozoic provinces, except where thinner in areas probably affected by Mesozoic extension associated with rifting of the Labrador Sea. Dipping reflectors in the mantle are commonly associated with strong lower-crustal dipping reflections in a manner similar to that observed in some modern orogens. The ECSOOT data show that Proterozoic crust in this area has structural forms comparable with those of modern orogens and, inferentially, its tectonic development was controlled by very similar collisional processes.